Microwave Absorption Characteristics Of Some Ferrite-filled Polymer Composites - Fadzidah Binti Mohd Idris; Mansor Hashim; Ismayadi Ismail; Idza Riati Ibrahim; Masni Manap; Mohd Shamsul Ezzad Shafie (Trans Tech Publications, Switzerland, 2024)
Prior to their use for microwave absorption, different compositions of NixZn1-xFe2O4 (x = 0.5, 0.6, 0.7 and 0.8) were prepared via mechanical alloying and sintering. X-ray diffractometry (XRD) was used to investigate the crystalline phase formation. Scanning transmission electron microscopy (STEM) and field emission electron microscopy (FeSEM) were used to investigate the particle size and surface morphology respectively. The complex-permeability components, ?? and ??, were also measured using an Agilent 4291B material analyzer from 1 MHz to 1 GHz. From the XRD results it is shown that at 900oC the full phase of nickel zinc ferrite was formed. The ?? values suggest that the ferrite sample can absorb well microwave energy for frequencies 1 MHz to 1 GHz and higher. This is proved by microwave absorption measurements carried out up to 12 GHz.